Cost Optimization of Formwork Using Value Engineering Techniques in Building Projects - Vansya, Muhammad Lawdy Dhiyaa; Kuncaravita, Sekar Ayu; Bustamin, Maulidya Octaviani; Sujatmiko, Bambang; Zuraidah, Safrin; Nugroho, Wisnu Abiarto (Journal of Advanced Industrial Technology and Application, 2024)
Formwork is a temporary mold for concrete that shapes the concrete during the casting process until it reaches the desired strength according to standards. Besides considering the strength and ease of use, it is also important to consider the cost of formwork to be more economical. This study analyzes costs using value engineering techniques, where this analysis investigates project issues in a structured and systematic manner by eliminating unnecessary costs without compromising the project’s performance, aesthetics, and reliability. The results of the structural analysis comparison between conventional formwork and the full system, initially using conventional formwork, are processed using the full system alternative. This alternative was tested on column, beam, and floor slab formwork. Therefore, it is recommended for this project to replace the column, beam, and floor slab formwork because the costs are quite high. In this analysis, savings were achieved by using the full system formwork, which saved 72% on beam formwork, 64% on column formwork, and 73% on floor slab formwork per square meter.